Implementasi Sanksi Pidana Terhadap Anggota Kepolisian Sebagai Pelaku Pengguna Narkoba (Studi Kasus Satuan Brimob Polda Sumut) - Kelana Efendi; Dani Sintara (Albayan Journal of Islam and Muslim Societies, 2025)
Drug abuse has become a highly alarming form of crime in many countries, including Indonesia. Narcotics-related crimes have posed a serious threat to the survival of the nation and the state, as they have involved various groups of people, ranging from adults and children to law enforcement officers. In Indonesia, cases of narcotics and psychotropic substance abuse have increasingly raised concerns due to their expanding and pervasive impact. Despite the enforcement of strict legal sanctions—including the death penalty—the spread of such crimes has continued to escalate. The management of these offenses has been undertaken by law enforcement agencies, namely the police, prosecutors, judges, and correctional officers. However, it is deeply regrettable that the police, who are expected to help eradicate narcotics-related crimes, have themselves been implicated in drug abuse. This research was qualitative in nature and employed a normative-empirical research design. The normative-empirical approach was a research methodology that integrated normative legal elements with empirical or data-based components to provide a more comprehensive analysis. The results of this study indicated that the implementation of criminal sanctions against police officers involved in narcotics abuse consisted of two legal process stages. The first was the general criminal procedure, which included arrest, investigation, detention, transfer to the prosecutor’s office and the court, followed by trial and verdict. Once the general criminal process was completed, the offender was required to undergo a disciplinary and code of ethics hearing within the police institution.In the process of applying criminal sanctions to police officers involved in drug-related offenses, the Provost Division (Divpropam) faced internal challenges. These challenges included the limited number of personnel in the North Sumatra Mobile Brigade (Satbrimob Polda Sumut) who had received training in narcotics investigations, inadequate budget allocation for conducting investigations, and challenges in coordinating schedules with related parties during the investigation process